Floral features, pollination biology and breeding system of Chloraea membranacea Lindl. (Orchidaceae: Chloraeinae) - Sanguinetti, Agustin (2012)
Background and Aims: The pollination biology of very few Chloraeinae orchids has been studied to date, and most of these studies have focused on breeding systems and fruiting success. Chloraea membranacea Lindl. is one of the few non-Andean species in this group, and the aim of the present contribution is to elucidate the pollination biology, functional floral morphology and breeding system in native populations of this species from Argentina (Buenos Aires) and Brazil (Rio Grande do Sul State). Methods:Floral features were examined using light microscopy, and scanning and transmission electron microscopy. The breeding system was studied by means of controlled pollinations applied to plants, either bagged in the field or cultivated in a glasshouse. Pollination observations were made on natural populations, and pollinator behaviour was recorded by means of photography and video.Key ResultsBoth Argentinean and Brazilian plants were very consistent regarding all studied features. Flowers are nectarless but scented and anatomical analysis indicates that the dark, clavate projections on the adaxial labellar surface are osmophores (scent-producing glands). The plants are self-compatible but pollinator-dependent. The fruit-set obtained through cross-pollination and manual self-pollination was almost identical. The main pollinators are male and female Halictidae bees that withdraw the pollinarium when leaving the flower. Remarkably, the bees tend to visit more than one flower per inflorescence, thus promoting self-pollination (geitonogamy). Fruiting success in Brazilian plants reached 60·78 in 2010 and 46 in 2011. Some pollinarium-laden female bees were observed transferring pollen from the carried pollinarium to their hind legs. The use of pollen by pollinators is a rare record for Orchidaceae in general.ConclusionsChloraea membrancea is pollinated by deceit. Together, self-compatibility, pollinarium texture, pollinator abundance and behaviour may account for the observed high fruiting success. It is suggested that a reappraisal and re-analysis of important flower features in Chloraeinae orchids is necessary.